Nuclear PDCD4 Expression Predicts Good Clinical Outcome in Luminal A-Like and Luminal B-Like Breast Cancer Subtypes - Madera, Santiago (2020)
Hormone receptor-positive (HR+, estrogen and/or progesterone receptor-positive) and HER2-negative breast cancer (BC) subtype is a biologically heterogeneous entity that comprises 70% of BCs. This subtype includes both luminal (Lum) A- and B-like subtypes, which have differences in prognosis and sensitivity to endocrine therapies. The development of biomarkers guiding treatment decisions in these settings is required. Tumor suppressor PDCD4 (programmed cell death 4), which can be found both in the nucleus (NPDCD4) or the cytoplasm (CPDCD4), inhibits tumor growth and metastasis, and its loss is associated with poor prognosis in solid tumors. To explore the clinical relevance of PDCD4 in BC, we analyzed its expression by immunohistochemistry in a cohort of 619 patients with primary invasive BC. We found that 34.7% of patients showed NPDCD4 and 21.3% showed CPDCD4. NPDCD4 positivity, but not CPDCD4, was associated with lower clinical stage (P = 0.0003), with presence of more differentiated tumors (P = 6.4x10-6), and with estrogen and progesterone receptor (PR) expression (P = 9.2x10-9 and P = 2.8x10-9, respectively). Kaplan-Meier analysis revealed that NPDCD4 expression was associated with a longer overall survival (OS) and disease-free survival (DFS) in LumA-like (P = 0.008 and P = 0.028, respectively) and LumB-like (P = 0.004 and P = 0.012, respectively) subtypes. Interestingly, patients with LumB-like tumors displaying NPDCD4 presented estimated OS and DFS rates similar to the ones observed in patients with LumA-like tumors also expressing NPDCD4, indicating that its presence improves the clinical outcome of LumB-like patients. Multivariate Cox regression analysis identified NPDCD4 as an independent predictor of good clinical outcome in both LumA-like (HR: 0.45, 95% CI 0.22-0.96, P = 0.038) and LumB-like (HR: 0.28, 95% CI 0.10-0.80, P = 0.018) subtypes. We validated our results by in silico analysis using expression data from the METABRIC cohort. Bioinformatics analysis of BC cells from the Cancer Cell Line Encyclopedia revealed a positive correlation between PDCD4 and PR expression (P = 0.015). Since LumB-like tumors present a higher risk of resistance to endocrine therapy and both PR and PDCD4 levels in this subtype are lower than in the LumA-like one, we postulated that the presence of PR may modulate PDCD4 expression. Silencing of PR expression in HR+ cells decreased PDCD4 protein levels while reconstitution of PR in a PR-null cell line increased them, confirming PR requirement for PDCD4 modulation. In line with PDCD4 physiological function, its knockdown increased cell migration capability of HR+ BC cells, whereas its restoration led to a decrease in cell migration of HR-negative BC models. Our findings identified NPDCD4 positivity as a novel biomarker of clinical outcome in LumA- and B-like subtypes and revealed PDCD4 reconstitution as a novel therapeutic strategy in BC.